2000
DOI: 10.15760/etd.1830
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrates and Excessive Fine Sediment Conditions in Oregon Coastal Streams

Abstract: The Pacific Coastal ecoregion contains large tracts of economically important forestlands that also serve as critical stream habitat for endangered Salmonids. Excessive fine sediment deposition in streams of this region is a major environmental concern in the region but difficult to measure directly. The use of stream invertebrates to monitor fine sediment conditions in streams requires careful consideration of several important factors that complicate their use as bioindicators including high spatial and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 103 publications
(203 reference statements)
1
2
0
Order By: Relevance
“…All the assemblages had some taxa that responded positively to increases in substrate size (e.g., sensitive native taxa) and some taxa responded negatively. These responses illustrate the critical importance of substrate size as a medium for stream biota and of the potential impacts of small increases in fine sediment to organisms evolved for relatively clean, high-gradient PNW streams (Munn et al, 2009;Edwards, 2014;Hubler et al, 2016). Dissolved oxygen is another critical factor affecting all biology in streams and the three assemblages sampled in this study all showed assemblage level response as minimum daytime DO values increased above ca.…”
Section: Effect Of Drought On Multi-stressorssupporting
confidence: 51%
See 1 more Smart Citation
“…All the assemblages had some taxa that responded positively to increases in substrate size (e.g., sensitive native taxa) and some taxa responded negatively. These responses illustrate the critical importance of substrate size as a medium for stream biota and of the potential impacts of small increases in fine sediment to organisms evolved for relatively clean, high-gradient PNW streams (Munn et al, 2009;Edwards, 2014;Hubler et al, 2016). Dissolved oxygen is another critical factor affecting all biology in streams and the three assemblages sampled in this study all showed assemblage level response as minimum daytime DO values increased above ca.…”
Section: Effect Of Drought On Multi-stressorssupporting
confidence: 51%
“…6). Substrate size is a well-known important determinant of invertebrate abundance and diversity, with highest diversity in the mid-size ranges (large gravels to cobbles) and the lowest abundance and diversity near the two extremes, sand and bedrock (Minshall, 1984;Munn et al, 2009;Relyea, et al, 2012;Edwards, 2014;Waite, 2014;Hubler et al, 2016).…”
Section: Invertebrate Assemblage Response To Stressorsmentioning
confidence: 99%
“…At least 16 EPT genera of macroinvertebrates occur in this region (Supporting Information S3 Table). As these taxa are sensitive to suspended sediment increase and fine sediment deposition (nine of them highly sensitive), they are often considered as indicators of good water quality, and sensitive to environmental changes [35,42] such as fine sediment deposition [43]. These taxa occurred with higher abundance on north-bank deltas than on south-bank deltas, although the differences were not significant.…”
Section: Periphyton and Macroinvertebrates South Versus North Bankmentioning
confidence: 99%